Clinical and Translational Allergy - Grattan, Clive; Bousquet, Jean
Clinical and Translational Allergy, one of several journals in the portfolio of the European Academy of Allergy and Clinical Immunology, provides a platform for the dissemination of allergy research and reviews, as well as EAACI position papers, task force reports and guidelines, amongst an international scientific audience. Clinical and Translational Allergy accepts clinical and translational research in the following areas and other related topics: asthma, rhinitis, rhinosinusitis, drug hypersensitivity, allergic conjunctivitis, allergic skin diseases, atopic eczema, urticaria, angioedema, venom hypersensitivity, anaphylaxis, food allergy, immunotherapy, immune modulators and biologics, animal models of allergic disease, immune mechanisms, or any other topic related to allergic disease. Beyond original research, Clinical and Translational Allergy also accepts structured reviews as well as opinion based reviews, and different position publications from EAACI or its National Societies. Open access publishing enables free access to all content ensuring a wide dissemination of articles; the electronic format and expert peer review allows for very rapid publication. Clinical and Translational Allergy is an international journal reaching out far beyond the borders of Europe, and invites clinicians and researchers from all countries of the world to contribute.